2020
DOI: 10.1002/art.41396
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Epigenetic Regulation by Identifying Functional cis‐Acting Long Noncoding RNAs and Their Targets in Osteoarthritic Articular Cartilage

Abstract: Objective To identify robustly differentially expressed long noncoding RNAs (lncRNAs) with osteoarthritis (OA) pathophysiology in cartilage and to explore potential target messenger RNA (mRNA) by establishing coexpression networks, followed by functional validation. Methods RNA sequencing was performed on macroscopically lesioned and preserved OA cartilage from patients who underwent joint replacement surgery due to OA (n = 98). Differential expression analysis was performed on lncRNAs that were annotated in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Moreover, mechanical stress gives promise to the novel lncRNA expression, and the number of the novel DELs was more than 10-fold of the known DELs, which suggests that this part is more responsive to mechanical stress in the lncRNA transcriptome. Indeed, the roles of lncRNAs are highlighted in chondrocyte biology and OA pathogenesis ( Tu et al, 2020 ; van Hoolwerff et al, 2020 ), such as lncRNA Pvt1 ( Li et al, 2017 ). In spite of the fact that increased Pvt1 is proven to be a promoter of chondrocyte apoptosis contributing OA, we found that Pvt1 was decreased instead in our system, suggesting that apoptosis might not be robustly induced by this mechanical stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mechanical stress gives promise to the novel lncRNA expression, and the number of the novel DELs was more than 10-fold of the known DELs, which suggests that this part is more responsive to mechanical stress in the lncRNA transcriptome. Indeed, the roles of lncRNAs are highlighted in chondrocyte biology and OA pathogenesis ( Tu et al, 2020 ; van Hoolwerff et al, 2020 ), such as lncRNA Pvt1 ( Li et al, 2017 ). In spite of the fact that increased Pvt1 is proven to be a promoter of chondrocyte apoptosis contributing OA, we found that Pvt1 was decreased instead in our system, suggesting that apoptosis might not be robustly induced by this mechanical stress.…”
Section: Discussionmentioning
confidence: 99%
“…To rationalize the lncRNAs most important in OA, van Hoolwerff et al. established lncRNA-mRNA co-expression networks using paired (lesion vs intact cartilage) RNA-seq data from almost 100 OA patients 58 . This identified 5,053 robustly expressed lncRNAs, of which 191 were significantly differentially expressed.…”
Section: Epigeneticsmentioning
confidence: 99%
“…This study pointed out 191 differentially expressed lncRNAs in degraded cartilage and demonstrated the importance of intergenic and antisense lncRNA in osteoarthritis pathophysiology. The authors also indicated P3H2-AS1 lncRNA as a potential preclinical target through regulation of its sense gene P3H2 [ 15 ]. Another study focused on microRNAs and their interactions with mRNAs by comparing the synovium between five osteoarthritis patients and three healthy controls.…”
Section: Transcriptomicsmentioning
confidence: 99%